Building Brand Loyalty through Halal Marketing Strategy: Analysis of the Role of Halal Awareness and Product Knowledge with Purchase Intention as an Intervening Variable - Azlan Azhari; Amrial Amrial; Hasnidar Hasnidar (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of Halal Awareness and Product Knowledge on Purchase Intention and its impact on Brand Loyalty of halal cosmetic products. This research employs a quantitative approach using the accidental sampling method, where respondents consist of consumers who have purchased and used halal cosmetic products. A total of 100 respondents participated in this study. Data were collected through online questionnaires and analyzed using the Partial Least Squares (PLS) method with SmartPLS 3 software. The results indicate that Halal Awareness and Product Knowledge have a positive and significant effect on Purchase Intention. Furthermore, Purchase Intention has a positive and significant effect on Brand Loyalty. Halal Awareness and Product Knowledge also have a positive and significant direct effect on Brand Loyalty. In addition, the indirect effect analysis reveals that Purchase Intention significantly mediates the influence of Halal Awareness and Product Knowledge on Brand Loyalty. These findings highlight the crucial mediating role of Purchase Intention in linking halal awareness and product knowledge with halal cosmetic brand loyalty. Therefore, halal cosmetic manufacturers are encouraged to continuously strengthen the communication of halal values ​​and product education to build strong purchase intention and drive sustainable brand loyalty.